Nationwide distribution and factors related to indoor fine particulate matter concentrations in subway stations in Korea: Results of first-year measurement - Su Jung Park; Jeonghoon Kim; In-Keun Shim; Jongchun Lee (Environment International)
This study assessed the seasonal distribution and factors associated with PM2.5 in nationwide subway stations in Korea. A total of 229,644 data points collected over one year were used to determine one-day PM2.5 concentrations from 642 subway stations. The geometric mean of indoor PM2.5 concentrations was 26.6 µg/m3. PM2.5 concentrations were higher in the Seoul metropolitan area (SMA) compared to non-Seoul metropolitan areas (NSMA), with the highest level occurring in winter, followed by spring, fall, and summer, similar to the trend observed for outdoor PM2.5 concentrations. In SMA, PM2.5 concentrations were significantly associated with the operation year, number of air cleaners on platforms, and number of passengers. These findings may help in the development of national strategies for managing indoor PM2.5 concentrations in subway stations, taking into account spatial and temporal factors.